1997
DOI: 10.1046/j.1365-2265.1997.2171021.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the putative inhibitor of the insulin receptor tyrosine kinase PC‐1 in dermal fibroblasts from patients with syndromes of severe insulin resistance

Abstract: The results indicate that PC-1 over-expression does not appear to contribute to the insulin resistant state of pseudo-acromegalic patients. The finding of normal insulin receptor tyrosine kinase activity in these subjects suggests that the site of defective insulin signalling is likely to be distal to the receptor. The unexpected finding that PC-1 activity, protein and mRNA were all dramatically reduced in patients with lesions early in the insulin signalling cascade provides further evidence for a link, albei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Conversely, PC-1 expression is reduced in cells with severe forms of insulin resistance due to receptor or postreceptor downstream genetic defects (30). Taken together, these data indicate that PC-1, rather than simply being an inhibitor of insulin action, is likely to be a fine tuner of the modulation of the insulin receptor.…”
Section: Discussionmentioning
confidence: 47%
“…Conversely, PC-1 expression is reduced in cells with severe forms of insulin resistance due to receptor or postreceptor downstream genetic defects (30). Taken together, these data indicate that PC-1, rather than simply being an inhibitor of insulin action, is likely to be a fine tuner of the modulation of the insulin receptor.…”
Section: Discussionmentioning
confidence: 47%
“…G o l d fine and colleagues (21)(22)(23)(24) reported several studies showing the association of high PC-1 expression with defective insulin action in human tissues. However, Whitehead et al (30) reported no increase in PC-1 expression level in dermal fibroblasts from patients with syndromes of insulin resistance. In addition, it was shown that PC-1 is markedly (~10-fold) overexpressed in the tissues as well as cultured skin fibroblasts from the patients of Lowe's syndrome (31).…”
Section: Discussionmentioning
confidence: 97%
“…However, the role of PC-1, if any, in insulin resistance has been highly controversial [81][82][83]. It has been suggested that the inhibition of phosphorylation of the insulin receptor by PC-1 is an in vitro artifact due to destruction of ATP [81], but this mechanism obviously cannot apply in the case where the enzymic activity of PC-1 has been abolished by mutagenesis of the active site threonine [80].…”
Section: Pc-1 and Insulin Resistancementioning
confidence: 98%